Muscle activity during dryland swimming while wearing a triathlon wetsuit - Agnelli, C.; Mercer, J. A. (International Journal of Kinesiology & Sports Science, 2018)
Background: Triathletes typically wear a wetsuit during the swim portion of an event, but it is not clear if muscle activity is influenced by wearing a wetsuit. Purpose: To investigate if shoulder muscle activity was influenced by wearing a full-sleeve wetsuit vs. no wetsuit during dryland swimming. Methods: Participants (n=10 males; 179.1±13.2 cm; 91.2±7.25 kg; 45.6±10.5 years) completed two dry land swimming conditions on a swim ergometer: No Wetsuit (NW) and with Wetsuit (W). Electromyography (EMG) of four upper extremity muscles was recorded (Noraxon telemetry EMG, 500 Hz) during each condition: Trapezius (TRAP), Triceps (TRI), Anterior Deltoid (AD) and Posterior Deltoid (PD). Each condition lasted 90 seconds with data collected during the last 60 seconds. Resistance setting was self-selected and remained constant for both conditions. Stroke rate was controlled at 60 strokes per minute by having participants match a metronome. Average (AVG) and Root Mean Square (RMS) EMG were calculated over 45 seconds and each were compared between conditions using a paired t-test (a=0.05) for each muscle. Results: PD and AD AVG and RMS EMG were each greater (on average 40.0% and 66.8% greater, respectively) during W vs. NW (p<0.05) while neither TRAP nor TRI AVG or RMS EMG were different between conditions (p>0.05). Conclusion: The greater PD and AD muscle activity while wearing a wetsuit might affect swimming performance and /or stroke technique on long distance event.